Psychosocial factors and dating violence: a review of the literature - Shalini Munusamy; Norhameza Ahmad Badruddin; Chong Sheau Tsuey; Hilwa Abdullah @ Mohd Nor; Mohammad Rahim Kamaluddin (Penerbit Universiti Kebangsaan Malaysia, 2024)
Dating violence is a major source of concern among the general population. Previous literature reviews have studied many other risk factors and dyadic implications of dating violence, but there has been very little research done in diverse elements of psychosocial factors linked to dating violence. The articles related to the term’s psychosocial factors (personality traits, attachment style and loneliness) and we looked for phrases linked to dating violence (aggression in romantic partnerships, violence in intimate relationships). The studies for this literature review must be from original studies with any gender sampling and should be written in English. This review included 27 papers that met the criteria for inclusion. The findings of this literature analysis revealed inconsistent results regarding the association between psychosocial factors and violent behaviour in romantic relationships, with some studies unable to detect such links. These findings are explored in terms of current gaps in the literature as well as suggested future research areas. The implication of this study can help in understanding the psychosocial factors that form the basis of relational aggression in romantic relationships and as a proactive step to avoid from being a victim of relational aggression.